JOHANNINE WOMEN AS PARADIGMS IN THE INDIAN CONTEXT - J. Thomaskutty (Acta Theologica)
John’s portrayal of women is unique as they are viewed as paradigms over against the negative perceptions concerning women in the Mediterranean world. The Johannine women demonstrate their leadership qualities, brave movements, apostolic roles, and devotion to Jesus even in the challenging situations. Women’s positive role and status in the Gospel of John enable us to understand them not merely as passive actors, but as active interlocutors and dialogue partners. Persons such as the mother of Jesus, the Samaritan woman, Mary and Martha of Bethany, and Mary Magdalene appear in the Gospel of John as representative figures and rhetorical characters. The Johannine narrator foregrounds the women characters as they use their freedom in both the Sitz-Im-Leben Jesu and the Sitz-Im-Leben Kirche. The Gospel of John is also interlocked with the Sitz-Im-Leben Indien to exemplify the evangelist’s gnomic linguistic and literary artistry.